Heritage Tourism Resilience and Sustainable Performance Post COVID-19: Evidence from Hotels Sector - Alaa M. S. Azzaz; Ibrahim A. Elshaer (Heritage, 2024)
Heritage tourism in Egypt, differentiated by its distinctive ancient wonders and cultural prosperity, has faced numerous challenges through its history, with political unrest, economic fluctuations, and, most recently, the global COVID-19 pandemic. This research paper investigates the dynamic interplay between planned and adopted resilience within the hotel sector in Egyptian heritage sites and their consequential effects on both social and economic sustainability. A quantitative research method was employed to empirically explore these dynamics. A structured questionnaire was distributed to 550 top and middle managers in hotels located in heritage sites, capturing insights into their perspectives on planned and adopted resilience. The collected data underwent rigorous analysis utilizing “partial least squares structural equation modeling” (PLS-SEM), providing a robust foundation for drawing meaningful conclusions. Findings from the research underscore the necessity of aligning planned and adopted resilience to generate sustainable social and economic performance. The synthesis of planned and adopted resilience was revealed to be pivotal in generating sustainable social and economic performance for hotels. This synthesis catalyzes the hotels’ ability to mitigate uncertainties, adjust to changing environment, and ensure long-term viability. This research might contribute to the current literature by suggesting industry-specific awareness for the reciprocal relationship between planned and adopted resilience in the hotel businesses and their combined influence on both sides of sustainability (social and economic). The findings provide actionable recommendations for hotel management, policymakers, and industry stakeholders to enhance resilience, foster social cohesion, and ensure the economic sustainability of heritage tourism in an everchanging environment.